Posterior malleolar fractures: A CT guided incision analysis. (June 2020) - Gandham, Surya; Millward, Graham; Molloy, Andrew P.; Mason, Lyndon W.
Highlights: The majority of type 2A fractures were assessed to be best approached through the posterolateral incision. For type 2B fractures, almost 2/3rds were agreed to be accessed most appropriately through a combined medial posteromedial and posterolateral approach. Type 3 fractures were assessed to be best approached through the PM approach. Abstract: Aim: The aim of this study was to determine the most appropriate approaches for fixation of each type and fragment of posterior malleolar fractures. Materials and methods: A retrospective analysis of a prospectively collected database was performed on 141 posterior malleolar fractures. On the CT scan axial slice, a clock face was drawn using the posterolateral corner of the tibia as the centre and the Achilles tendon as the 6 o'clock axis. A box was then drawn from the fracture plane, with 90-degree lines corresponding to the medial perpendicular line (MPL) and lateral perpendicular line (LPL) extremity of the fracture and a central perpendicular line (CPL) (i.e. orthogonal central plane, for optimum screw placement). It was recorded where the MPL, LPL and CPL exited the clock face. All fracture patterns were further assessed by both senior authors regarding their choice of approach based on CPL and all variances resolved by discussion. Results: The LPL was equivalent across the groups (except for the 2B medial fragments), indicating a consistent posterolateral corner fragment throughout the posterior malleolar sub types (p = 0.25). The medial aspect (MPL) of the type 1, type 2A and posterolateral fragments of type 2B were equivalent. The MPL of type 3 fractures was significantly more medial than type 1 and 2A fractures (p < 0.05), with the medial extremes of the type 2B posteromedial fragment being further medial. The majority of type 2B fractures (2/3rds) were determined to be best accessed through a combined posterolateral and medial posteromedial approach, with the other third via the posteromedial approach. Almost all type 3 fractures could be appropriately accessed through the PM approach. Conclusion: This study concludes that the extent of each subtype of posterior malleolar fractures are consistent. To fully expose each fracture differing incisions are necessary and should be in the skill mix for surgeons treating these fractures. Level of evidence: 4.